Extreme Diversity of Diplonemid Eukaryotes in the Ocean - Flegontova, Olga; Flegontov, Pavel; Malviya, Shruti; Audic, Stephane; Wincker, Patrick; de Vargas, Colomban; Bowler, Chris; Lukeš, Julius; Horák, Aleš (Current biology, 2016)
The world's oceans represent by far the largest biome, with great importance for the global ecosystem [1-4]. The vast majority of ocean biomass and biodiversity is composed of microscopic plankton. Recent results from the Tara Oceans metabarcoding study revealed that a significant part of the plankton in the upper sunlit layer of the ocean is represented by an understudied group of heterotrophic excavate flagellates called diplonemids [5, 6]. We have analyzed the diversity and distribution patterns of diplonemid populations on the extended set of Tara Oceans V9 18S rDNA metabarcodes amplified from 850 size- fractionated plankton communities sampled across 123 globally distributed locations, for the first time also including samples from the mesopelagic zone, which spans the depth from about 200 to 1,000 meters. Diplonemids separate into four major clades, with the vast majority falling into the deep-sea pelagic diplonemid clade. Remarkably, diversity of this clade inferred from metabarcoding data surpasses even that of dinoflagellates, metazoans, and rhizarians, qualifying diplonemids as possibly the most diverse group of marine planktonic eukaryotes. Diplonemids display strong vertical separation between the photic and mesopelagic layers, with the majority of their relative abundance and diversity occurring in deeper waters. Globally, diplonemids display no apparent biogeographic structuring, with a few hyperabundant cosmopolitan operational taxonomic units (OTUs) dominating their communities. Our results suggest that the planktonic diplonemids are among the key heterotrophic players in the largest ecosystem of our biosphere, yet their roles in this ecosystem remain unknown.
Keywords: plankton; metabarcoding; ekosystém; sekvenční analýza RNA; diversity; taxonomické DNA čárové kódování; biodiverzita; oceány a moře; Aquatic Organisms; diplonemids; Euglenozoa; cosmopolitan; Sequence Analysis, RNA; RNA ribozomální 18S; Plankton; Tara Oceans; RNA, Ribosomal, 18S; vodní organismy; Biodiversity; RNA protozoální; DNA Barcoding, Taxonomic; Ecosystem; RNA, Protozoan; Oceans and Seas